Financial product development and members' voluntary saving behavior in saving and credit cooperatives in Tigray: A case study in Endamohoni Woreda - Solomon Abadi Dirar; Tekeste Berhanu; Dereje Getachew; Hossein Azadi (Cogent Economics & Finance, 2017)
This survey study aimed to analyze the financial product development and members' saving behavior in saving and credit cooperative societies (SACCOs) in the Endamohoni Woreda district in Tigary, Ethiopia. Using cluster random sampling, the study was conducted in four SACCOs and selected 96 members from the SACCOs. Data were collected using structured questionnaire and focus group discussion. Binary logistic regression was employed to identify and analyze the determinants of members' voluntary savings. Results showed that voluntary savings are significantly affected by age, marital status, educational level, number of dependents, access to training, household size, safety, and years of membership in SACCOs. The results also showed that the SACCOs provide a very limited range of financial products to their members. Yet, the survey indicated that the members have access to other formal financial institutions, other than their own SACCOs given that their access to loans was easier and service delivery was faster in those financial institutions than the SACCOs. Therefore, the SACCOs and the concerned bodies regarding the development promotion of SACCOs need to take into consideration the aforementioned factors when designing policies and strategies that aim at enhancing voluntary savings of the SACCOs' members.
Keywords: 330; voluntary savings; financial product development; saving behavior; SACCOs members; binary logistic model